2017
DOI: 10.1053/j.gastro.2017.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin Induces Nuclear Export and Proteasome Degradation of Menin in Enteric Glial Cells

Abstract: Background The Multiple Endocrine Neoplasia, type 1 (MEN1) locus encodes the nuclear tumor suppressor protein menin. MEN1 mutations frequently cause neuroendocrine tumors (NETs) such as gastrinomas, remarkable for their predominant duodenal location and local metastasis at the time of diagnosis. Diffuse gastrin cell hyperplasia precedes the appearance of MEN1 gastrinomas, which develop within submucosal Brunner’s glands. We show here that loss of menin in enteric glial cells induces gastrin expression. Aim T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
71
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(75 citation statements)
references
References 44 publications
1
71
1
Order By: Relevance
“…Following a century of evolving terminology, gastric carcinoids, the term most used by clinicians and the subject of this paper, are now more accurately and definitively described as neuroendocrine tumors (NETs), a subgroup of gastro-entero-pancreatic endocrine tumors (GEPs), and hence formally designated GEP-NETs. For the purpose of this paper, however, I use the term "gastric carcinoid" (although archaic) to describe those NETS that are limited to the stomach, excluding those in the duodenum and small intestine, which may have a different pathogenesis [1,2]. Their proximate cells of origin appear to be enterochromaffin-like (ECL) cells, which like most NETs arise from locally multipotent gastrointestinal stem cells, and not from the neural crest as earlier hypothesized [3].…”
Section: Introductionmentioning
confidence: 99%
“…Following a century of evolving terminology, gastric carcinoids, the term most used by clinicians and the subject of this paper, are now more accurately and definitively described as neuroendocrine tumors (NETs), a subgroup of gastro-entero-pancreatic endocrine tumors (GEPs), and hence formally designated GEP-NETs. For the purpose of this paper, however, I use the term "gastric carcinoid" (although archaic) to describe those NETS that are limited to the stomach, excluding those in the duodenum and small intestine, which may have a different pathogenesis [1,2]. Their proximate cells of origin appear to be enterochromaffin-like (ECL) cells, which like most NETs arise from locally multipotent gastrointestinal stem cells, and not from the neural crest as earlier hypothesized [3].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these important functions, however, their impact on the development of colorectal cancer (CRC) has not been well investigated. Nevertheless, a number of observations suggest that these cells may be involved in modulating tumor development, as they are implicated in the origin of gastrinomas (18), they can produce inflammatory molecules (19)(20)(21), and their tissue organization is disrupted in human neoplasias (13,22). Moreover, megacolon, which can develop following ablation of the ganglia in the gut, appears to protect against carcinogenesis (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…A recent exciting study has shown the colocalization of gastrin with several glial markers such as GFAP, p75 (low‐affinity neurotrophin receptor), and S100b in duodenal gastrinomas (Sundaresan et al, ). Therefore, EGCs or their precursors might be transformed to cancer stem cells.…”
Section: Introductionmentioning
confidence: 99%